Preparation and characterization of SrBi2Nb2O9 thin films made by polymeric precursors - Zanetti, S. M.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Springer Nature, 1998)
A polymeric precursor solution was employed in preparing SrBi2Nb2O9 (SBN) powder and thin films dip coated onto Si(100) substrate. XRD results show that the SBN perovskite phase forms at temperatures as low as 600°C through an intermediate fluorite phase. This fluorite phase is observed for samples heat-treated at temperatures of 400 and 500°C. After heat treatment at temperatures ranging from 300 to 800°C, thin films were shown to be crack free. Grazing incident angle XRD characterization shows the occurrence of the fluorite intermediate phase for films also. The thickness of films, measured by MEV, was in the order of 80-100 nm.
Keywords: Fluorspar; Heat treatment; Perovskite; Phase transitions; Polymers; Strontium compounds; Thickness measurement; Thin films; X ray diffraction analysis; Strontium bismuth niobate; Dielectric films